Kerusakan Fatik pada Baut dan Mur Roda Kendaraan Ringan untuk Operasi Tambang Batubara [Fatigue Failure of Wheel Studs and Nuts of Light Vehicles Used in Coal Mine Operation] - Adnyana, D. N (Jurnal Metalurgi, 2017)
Light vehicle is a potentially useful and efficient mode of transportation to be utilized in supporting the coal mine operation. However, due to the harsh road condition at the mine site, many light vehicles presently used are frequently experiencing a number of incidents caused by loose wheel. The occurrence of this loose wheel is very much related with some broken or damaged wheel studs and/or nuts of the vehicle. Type of failure and factors that may have caused the damage of the wheel studs and/or nuts of the vehicles are discussed in this paper. The metallurgical assessment was conducted by preparing a number of specimens from the damaged and undamaged wheel studs and nuts of the vehicles. Various laboratory examinations were performed including macroscopic examination, chemical composition analysis, metallographic examination, hardness test and SEM (scanning electron microscopy) examination equipped with EDS (energy dispersive spectroscopy) analysis. In addition, torsion test was also conducted on several new studs and nuts to measure the relationship between the torque and angular displacement. Results of the metallurgical assessment obtained show that the damaged wheel studs have experienced fatigue crack or fracture that was caused by load cycling under unidirectional bending at a low nominal stress. Most of the fatigue cracks were originated from the common fatigue initiation sites at the thread root of the stud. There are four possible factors that may have contributed to the acceleration of fatigue failure on the wheel studs or nuts of the light vehicles, either singly or in combination, including improper use of the vehicle, improper material of the wheel stud, improper material of the wheel and/or incorrect installation of the stud and wheel joint.